2008
DOI: 10.1086/589309
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus–Induced Secretion of Inflammatory Chemokines Preferentially Recruits NKG2A+CD8+T Cells

Abstract: In patients with hepatitis C, a loss-of-function mutation of chemokine receptor CCR5 (CCR5Delta32) has been shown to be associated with spontaneous viral clearance and lower levels of hepatic inflammation. In the present study, we show that CCR5 is coexpressed with the inhibitory NKG2A receptor on CD8(+) T cells. Consequently, CCR5(+) T cells were highly susceptible to NKG2A-mediated inhibition of cytotoxic activity and NKG2A(+) lymphocytes were preferentially attracted by CCR5 ligands induced by hepatitis C v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…The three receptors share chemokine ligands: CCR5 interacts with CCL3, CCL4, CCL5 and CCL8; CCR2 with CCL2, CCL13, CCL7 and CCL8; and CCR1 with CCL3, CCL5, CCL7, CCL23 and CCL14-16 [3,89] . All of these chemokines have been detected in the liver [51,56,[90][91][92] . CCR1, CCR2 and CCR5 expression is characteristic of memory T cells and CCR5 is expressed on Th1 cells [89,93] , with particularly high frequencies detected in the human liver [51,55,90] .…”
Section: Ccr5 and Ccr1/ccl5 And Liver Inflammationmentioning
confidence: 99%
“…The three receptors share chemokine ligands: CCR5 interacts with CCL3, CCL4, CCL5 and CCL8; CCR2 with CCL2, CCL13, CCL7 and CCL8; and CCR1 with CCL3, CCL5, CCL7, CCL23 and CCL14-16 [3,89] . All of these chemokines have been detected in the liver [51,56,[90][91][92] . CCR1, CCR2 and CCR5 expression is characteristic of memory T cells and CCR5 is expressed on Th1 cells [89,93] , with particularly high frequencies detected in the human liver [51,55,90] .…”
Section: Ccr5 and Ccr1/ccl5 And Liver Inflammationmentioning
confidence: 99%
“…The receptors share chemokine ligands; CCR5 interacts with CCL3, CCL4, CCL5 and CCL8; and CCR2 interacts with CCL2, CCL13, CCL7 and CCL8 all of which have been detected in the liver30,80. CCR5 ligands are strongly expressed on portal endothelium81 and in murine models of graft versus host disease CCR5 and CCL3 support effector cell recruitment to portal tracts64.…”
Section: Adaptive Immune Response and T Cell Recruitment In Hcvmentioning
confidence: 99%
“…These T cells are attracted to the liver in response to CCR5 ligands induced by HCV E2 antigen. However engagement of the NKG2A receptor results in their inactivation demonstrating another mechanism by which HCV can manipulate chemokine networks to subvert effective immune responses80. The consequences of HCV on T cells can be unpredictable; for example although HCV-E2 binding to CD81 on CD8 T cells increases CCL5 secretion this causes autocrine desensitization of CCR5 and a loss of migratory capacity82.…”
Section: Adaptive Immune Response and T Cell Recruitment In Hcvmentioning
confidence: 99%
“…However, these relationships appear to be more complex. We recently showed that CCR5 (+) lymphocytes are characterized by a high expression of the inhibitory NK cell receptor NKG2A [21]. Therefore, these cells are very sensitive to NKG2A-mediated inhibition of cytotoxic function.…”
Section: Hcv and Ccr5mentioning
confidence: 99%